2009
DOI: 10.1111/j.1365-3059.2008.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Trichothecene mycotoxin genotypes ofFusarium graminearum sensu strictoandFusarium meridionalein wheat from southern Brazil

Abstract: A total of 82 fungal isolates was obtained from wheat kernel samples affected by fusarium head blight collected from 20 locations in southern Brazil. Polymerase chain reaction (PCR) assays were used to characterize trichothecene mycotoxin genotypes [deoxynivalenol (DON), nivalenol (NIV) and two acetylated derivatives of DON]. To identify isolates that producing DON and NIV, portions of the Tri13 gene were amplified. To identify 3-acetyl-deoxynivalenol (3-ADON) and 15-acetyl-deoxynivalenol (15-ADON) genotypes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
39
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 36 publications
12
39
0
11
Order By: Relevance
“…This isolate was identified to have a DON (Figure 3a) and 15-ADON (Figure 3b) genotype, which indicates that it has a potential to produce these mycotoxins. This data is in agreement with reports about the predominance of trichothecene genotypes for DON and 15-ADON in F. graminearum isolates from Argentina and Southern Brazil (RAMIREZ et al, 2006;SCOZ et al, 2009). The methodology recommended by the International Commission on Food Mycology (ICFM), a commission of the International Union of Microbiological Societies (IUMS), for isolation, enumeration, and identification of fungi from foods consists of techniques based on viable counting (dilution plating and direct plating) for detecting and quantifying fungal growth in foods (PITT; HOCKING, 2009).…”
Section: Resultssupporting
confidence: 93%
“…This isolate was identified to have a DON (Figure 3a) and 15-ADON (Figure 3b) genotype, which indicates that it has a potential to produce these mycotoxins. This data is in agreement with reports about the predominance of trichothecene genotypes for DON and 15-ADON in F. graminearum isolates from Argentina and Southern Brazil (RAMIREZ et al, 2006;SCOZ et al, 2009). The methodology recommended by the International Commission on Food Mycology (ICFM), a commission of the International Union of Microbiological Societies (IUMS), for isolation, enumeration, and identification of fungi from foods consists of techniques based on viable counting (dilution plating and direct plating) for detecting and quantifying fungal growth in foods (PITT; HOCKING, 2009).…”
Section: Resultssupporting
confidence: 93%
“…F. graminearum is also dominant in the United States and Canada (Starkey et al 2007;Gale et al 2007;Ward et al 2008;Schmale et al 2011), and is found on all continents with the exception of Antarctica (O'Donnell et al 2004;Aoki et al 2012;Backhouse 2014). While the species within the FGSC show a significant biogeographic structure (Aoki et al 2012), substantial species diversity has been observed in South America (Scoz et al 2009;Sampietro et al 2010;Umpiérrez-Failache et al 2013), Asia (Yli-Mattila et al 2009Suga et al 2008;Zhang et al 2012), Africa (Boutigny et al 2011;O'Donnell et al 2008) and New Zealand (Monds et al 2005). Long-distance dispersal and anthropogenic activities have the potential to alter regional pathogen composition as suggested by the recent discovery of significant populations of F. asiaticum, an Asian endemic that appears to be adapted to rice agroecosystems (Lee et al 2009), on wheat in major rice production areas of Louisiana and Uruguay .…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, a giberela em trigo é causada por espécies do complexo Fusarium graminearum, especialmente F. graminearum sensu stricto (Fgss) (SCOZ et al, 2009;ASTOLFI et al, 2012). Os danos ocasionados por giberela em trigo no Brasil incluem a redução no rendimento e a contaminação com as micotoxinas de desoxinivalenol (DON) e nivalenol (NIV) (CASA et al, 2004;DEL PONTE et al, 2012).…”
Section: Introductionunclassified
“…Os danos ocasionados por giberela em trigo no Brasil incluem a redução no rendimento e a contaminação com as micotoxinas de desoxinivalenol (DON) e nivalenol (NIV) (CASA et al, 2004;DEL PONTE et al, 2012). No Sul do Brasil, as populações de Fgss (a dominante, com 90% de frequência em isolamentos) e Fmer têm apresentado consistentemente genótipo tricoteceno15-A(acetil)DON, uma forma acetilada de DON, e NIV, respectivamente, o que sugere que podem produzir diferentes concentrações de DON e nivale nol (SCOZ et al, 2009;ASTOLFI et al, 2012). SPOLTI et al (2012a) , evidenciando que as populações produzem ambas as micotoxinas.…”
Section: Introductionunclassified